Effects of zinc oxide nanoparticles (ZnO NPs) synthesized from different plant leaf extracts on mealworm larvae Tenebrio molitor L.,1758 (Tenebrionidae: Coleopetera) - Omar, Saher T; Ali, wand K (Zanco Journal of Pure and Applied Sciences, 2024)
Synthesize of zinc nanoparticles adopted through a simple, and eco-friendly biosynthesis process, utilizing the eucalyptus ( Eucalyptus camaldulensis), river oak (Casuarina cunninghamiana) and dill (Anethum graveolens ) leaves as sources and evaluate the insecticidal effects of the produced zinc oxide nanoparticles against the mealworms Tenebrio molitor L.,1758.The produced ZnO nanoparticles were characterized by X-ray diffraction (XRD), UV–visible, and transmission electron microscopy (TEM). The laboratory research was carried out with feeding method (the leaf immersion in ZnO NPs solution with different concentrations). The mortality effects of all the three synthesized ZnO nanoparticles against the studied larval stage was recorded in various period of time. the results of the statistical analysis showed that there were significant differences in the average mortality rate according to plant consisting of zinc nanoparticle, in which the highest average of the larval mortality was obtained (61.83%) for river oak, with an average percentage of adult emergence (27.50 %). Similarly the LC50 values of the ZnO NPs derived from the used plants was showed a varying effect on the larvae of mealworm with feeding method and that this effect varied according to the plant species in which for the River oak was (396.27 ppm ), Eucalyptus plant (3630.78 ppm )and Dill plant was( 6280.58 ppm). This result concluded that Zinc Oxide Nanoparticles from plant sources has larvicidal properties but the most effective one was from River oak plant and they serve as eco-friendly an alternative to synthetic insecticides for controlling insect stages. Hence the biogenic Zinc Oxide Nanoparticles can be used as potential insecticidal agent for the studied insect.